Energetic, exergetic, and exergoeconomic analyses of beer wort production processes - Jemigbeyi, O. S.; Salau, T. A. O.; Oyewola, O. M. (Frontiers in Energy Research, 2024)
Energy efficiency strategies in industrial breweries examine the inefficiency of thermal systems from a thermodynamic perspective. However, understanding the costs of inefficiencies in systems, including non-thermodynamic costs, requires exergoeconomics. This study examined wort production in a standard Tier-1 brewery from the tripod of energy, exergy, and exergoeconomics analyses to assess the performance of brewing sections and to pinpoint components that contributed the most to exergy destruction and product cost rate. The energy analyses for the production system showed that the total specific energy for processing 10.05 tons of brew grains to 346.98 hl high-gravity wort was (86 ± 1) MJ/hl at an operational energy efficiency of 30.35%. The exergetic analyses showed that the cumulative exergetic destruction was 3.2737 MW, with the brewhouse section contributing 89.25% of the system’s inefficiencies. Also, the analyses showed that the wort kettle (42.7911%), mash tun (10.8086%), preheater (10.0683%), whirlpool (8.3522%), and adjunct kettle (6.2705) are the top five components with the highest rates of cumulative exergy destruction. The exergoeconomic analyses revealed that the cost rate of processing chilled wort was estimated to be 0.0681 USD/s per overall exergetic efficiency of 6.61%. The five most significant components are the wort kettle (53.70%), whirlpool (16.42%), mash filter (10.44%), mash tun (6.875%), and adjunct kettle (3.31%) based on the relative total cost increases for the production processes. Additionally, wet steam throttling resulted in a 2.51% increase in exergetic efficiency, a 1.60% drop in exergetic destruction rate, and a decrease in cost rates to 0.0675 USD/s.